Implementasi Kebijakan Program Makanan Bergizi di SD Kartika Manado - Sumilat, Juliana Margaretha; Tamalonggehe, Regina Marcela; Lasamahu, Laydi Nadine; Wewe, Yosefina; So’o, Maria Elisabeth Meyske (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to explain the implementation of the nutritious food program policy at Kartika Elementary School in Manado and analyze its impact on student health and eating habits. A qualitative case study approach was used, involving the principal, teachers, kitchen staff, and students as informants. Data were obtained through observations of communal mealtimes and in-depth interviews. The results indicate that the nutritious food program has been implemented quite well through the provision of balanced menus, regular meal schedules, and simple nutrition education incorporated into lessons. Teachers play an active role in monitoring and accompanying students during meals to ensure daily nutritional needs are met. The positive impact of this program is evident in increased student interest in healthy foods, increased energy during learning, and the development of better eating habits. However, several challenges remain, such as budget constraints, delays in food delivery, and menu variations that are not fully suited to student preferences. Improvements have been made by adjusting menus, coordinating with food providers, and increasing outreach to parents. Overall, the implementation of the nutritious food program policy at Kartika Elementary School in Manado is considered quite successful, supporting student health and readiness to learn